Inclusão Social: desafios da Pessoa com Deficiência no mercado de trabalho - Abreu, Lara Regina Rodrigues de (Universidade Federal do Tocantins, 2025)
This Course Conclusion Paper sought to understand the challenges and possibilities for the inclusion of people with disabilities in the job market, as well as the role of the social worker in this inclusion process. The study also highlights the particularities of the work carried out by the Association of Parents and Friends of the Disabled in the municipality of Miranorte in the state of Tocantins, thus understanding the local and regional reality. In order to carry out the analyses, the qualitative study, anchored in the historical dialectic method, used secondary sources of information from bibliographical research, specialized literature on the subject and public data such as the IBGE and PNAD Continua. From this perspective, the analyses reveal that even in the face of advances in terms of legislation and public policies, which guarantee rights and incentives for hiring people with disabilities, the reality faced by this segment of the population in the job market is still marked by issues related to professional qualifications, physical, social, cultural, gender and stigma barriers. We would also like to highlight the importance of Social Work and its intervention in defending the rights of people with disabilities, contributing to strengthening social policies and defending accessibility and equity, enabling access to rights and the inclusion of people with disabilities in the job market.